Study of Intelligent Photovoltaic Micro-grid and N+1 Control Pattern - 李志勇; 冯江华 (Kongzhi Yu Xinxi Jishu)
Aiming to improve the control ability of distributed generation including photovoltaic power system, the fundamental concepts and its relative technologies of intelligent photovoltaic micro-grid are studied. The configuration of micro-grid and the electrical characteristics of terminal equipments, such as distributed generator, power storage, power quality adjustor, are introduced and analyzed. An Intelligent micro-grid control pattern with N+1 nodes based on communication network is proposed. The information integration of energy management and the interactive control among the generation, storage and power consumer in the intelligent photovoltaic micro-grid are realized.